The game of baseball - Epstein, Sam, 1909-; Epstein, Beryl Williams, 1910-; Hays, Hobe. (Champaign, Ill. : Garrard Pub. Co., 1965)
Presents a short history of baseball.
Keywords: Baseball -- Juvenile literature; Baseball -- History